Detection and decontamination of Mycoplasma in cultured cells and viral strains - Glaucia Prado de Andrade; Natália Hettwer Pedroso; Alice Becker; Vinicius Soares dos Santos; Juciane Bonella; José Valter Joaquim Silva Júnior; Rudi Weiblen; Eduardo Furtado Flores (Ciência Rural)
ABSTRACT: Contamination of biological products with Mycoplasma spp. represents a major problem for laboratories and vaccine industry. Herein, we investigated Mycoplasma spp. contamination in cell cultures and viral strains maintained at the Virology Section of the Universidade Federal de Santa Maria and evaluated drugs and protocols for decontamination. Among 25 cell lines and primary cultures tested by PCR, 16 (64%) were contaminated. Fourteen bovine viral strains were also found contaminated, including three bovine viral diarrhea virus 1 (BVDV-1), two BVDV-2, four bovine alphaherpesvirus 1 (BoHV-1), one each: HoBiPeV, BoHV-2, BoHV-5, bovine parainfluenza virus 3 (bPI-3V) and bovine respiratory syncytial virus (BRSV). Two drugs (Plasmocin ® [P] and gentamicin [G]) were used individually or mixed for decontamination. Bovine (MDBK and CRIB cells), porcine (PK-15), rabbit (RK-13) and hamster (BHK-21) cell lineages were maintained in media containing the drugs and tested by PCR at weekly intervals. The combined P + G treatment was effective in eliminating Mycoplasma spp. from four cultures between days 35 and 42, followed by treatment with Plasmocin ® (3/4) and gentamicin alone (1/4). The CRIB cell line could not be decontaminated. After, a decontamination protocol of viral seeds was carried out, consisting of amplification in cell culture, centrifugation of the viral suspension, filtration, limiting dilution and culture in mycoplasma-free cells. The fourteen viral strains were decontaminated after 1 to 4 cycles of the protocol. Overall, we detected a high frequency of Mycoplasma spp. contamination in cell cultures and viral strains and successfully applied drugs and protocols for decontamination.